The Double Edge Sword of Testosterone’s Role in the COVID-19 Pandemic - Younis, Johnny S.; Skorecki, Karl; Abassi, Zaid (Frontiers in Endocrinology, 2021)
COVID-19 is a complex disease with a multifaceted set of disturbances involving several mechanisms of health and disease in the human body. Sex hormones, estrogen, and testosterone, seem to play a major role in its pathogenesis, development, spread, severity, and mortalities. Examination of factors such as age, gender, ethnic background, genetic prevalence, and existing co-morbidities, may disclose the mechanisms underlying SARS-CoV-2 infection, morbidity, and mortality, paving the way for COVID-19 amelioration and substantial flattening of the infection curve. In this mini-review, we focus on the role of testosterone through a discussion of the intricate mechanisms of disease development and deterioration. Accumulated evidence suggests that there are links between high level (normal male level) as well as low level (age-related hypogonadism) testosterone in disease progression and expansion, supporting its role as a double-edged sword. Unresolved questions point to the essential need for further targeted studies to substantiate these contrasting mechanisms.